2013
DOI: 10.1021/ef301916b
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Increase during the Depressurization of Partially Hydrate-Saturated Formations within the Stability Region

Abstract: Depressurization experiments of methane-hydrate-bearing sediments were conducted to measure changes within the hydrate stability region before dissociation started. Pore-filling hydrate with a saturation of about 40% was formed in water-saturated silica sand samples with a porosity of 0.4. The initial pressure was kept constant at around 14.5 MPa, and the initial temperature was varied between 281.3 and 283.7 K. When the samples were depressurized at rates ranging from −1.2 to −3.9 MPa/min, temperature increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…As such, care should be taken in selecting suitable grains to form representative synthetic hydrates for methane hydrate production studies, especially for studies conducted with the conventional P–V–T calculation without a sighting window, to ensure the usefulness of data reported in the literature. A representative approach would be to employ the excess water method by which water is added in excess to ensure that synthetic hydrates are formed between the interstitial pore spaces of the chosen porous media. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…As such, care should be taken in selecting suitable grains to form representative synthetic hydrates for methane hydrate production studies, especially for studies conducted with the conventional P–V–T calculation without a sighting window, to ensure the usefulness of data reported in the literature. A representative approach would be to employ the excess water method by which water is added in excess to ensure that synthetic hydrates are formed between the interstitial pore spaces of the chosen porous media. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…thermal stimulation, for economical gas production [125,139]. However, one recent work reported a temperature increase of 0.26-0.35 K during depressurization from a high pressure (14.5 MPa) [140]. The authors reasoned that the presence of free gas resulted in reformation of methane hydrate during gas production.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…However, this is highly probable in the natural environment given the fact that ambient conditions in nature will not be as easily manipulated as in a laboratory reactor and chances for hydrate re-formation always exist should the appropriate conditions exist at a different location during recovery [140].…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…The guest gases, such as methane molecules, are trapped in the water cavities at a low temperature and high pressure. With the increasing demand of oil and nature gas resources, there is an urgent need to search for an alternative energy. Nature gas hydrates (NGHs) found in permafrost and deep ocean sediments are of significant potential due to their enormous reserves. Different exploitive methods of nature gas hydrate from hydrate deposits have been proposed, namely, depressurization, thermal stimulation, , as well as thermodynamic inhibitor injection. , The depressurization method is considered the most promising in terms of economic efficiency. , …”
Section: Introductionmentioning
confidence: 99%
“…12,13 The depressurization method is considered the most promising in terms of economic efficiency. 14,15 The deposits of methane hydrate are generally divided into three classes, Class I (with underling free gas), Class II (with underling free-water), and Class III (single hydrate zone), 16,17 as shown in Figure 1. The hydrate dissociation of Class I and Class II has been studied by MRI; 18 it was found that liquid water hindered the output of methane gas during gas production.…”
Section: Introductionmentioning
confidence: 99%